2021
DOI: 10.3390/cancers13081950
|View full text |Cite|
|
Sign up to set email alerts
|

The Genomic Landscape of Lobular Breast Cancer

Abstract: Invasive lobular carcinoma (ILC) is the second most common breast cancer histologic subtype, accounting for approximately 15% of all breast cancers. It is only recently that its unique biology has been assessed in high resolution. Here, we present a meta-analysis of ILC sequencing datasets, to provide a long-awaited ILC-specific resource, and to confirm the prognostic value and strength of association between a number of clinico-pathology features and genomics in this special tumour type. We consider panel (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…Although some studies analyzing ILC have reported a similar frequency of CDH1 mutations in ILC, these studies did not select cases based on E-cadherin loss. 18 Our results suggested that mechanisms other than CDH1 mutations are frequently implicated in E-cadherin loss in IDLC.…”
Section: Discussionmentioning
confidence: 53%
“…Although some studies analyzing ILC have reported a similar frequency of CDH1 mutations in ILC, these studies did not select cases based on E-cadherin loss. 18 Our results suggested that mechanisms other than CDH1 mutations are frequently implicated in E-cadherin loss in IDLC.…”
Section: Discussionmentioning
confidence: 53%
“…Next, we tested the effect of dasatinib on mammary and gastric organoids lacking both Cdh1 and T p53 expression. These organoids were generated in order to more closely reflect the genetic complexity of advanced DGC and LBC which have Tp53 mutation frequencies of ~33% and ~7–18%, respectively [ 56 , 57 , 58 ]. The difference in the response of Tp53 −/− Cdh1 −/− gastric and mammary organoids to dasatinib was similar to that of Cdh1 −/− organoids ( Figure 4 E,F).…”
Section: Resultsmentioning
confidence: 99%
“…This has been explained by epigenetic silencing and/or transcriptional repression, but the relevance of these proposed alternative mechanisms has remained controversial [42,87,88]. Lack of a detectable CDH1 mutation may also be related to insufficient sequencing depth or low tumor cellularity [40,89]. In some instances, CDH1 missense mutations, in-frame deletions, and even truncating mutations can be associated with preserved E-cadherin expression [43,90].…”
Section: Ilc As a Morpho-molecular Entitymentioning
confidence: 99%
“…Histological grade G1 is associated with comparatively good short-term outcome, but the prognosis G2-and G3-differentiated cases is difficult to predict [61]. High grade ILC appears to be associated with worse outcome [61,73,89].…”
Section: Classic Ilcmentioning
confidence: 99%